Ancestral knowledge for the care of nature in the native community of Tutumberos - Huaman Tomanguilla, Jhony (2022)
The objective of this research was to interpret the ancestral knowledge for the care of nature of the native community of Tutumberos. The research design used was ethnographic, because the research has a qualitative approach, and attempts to explore and identify knowledge that is little known and studied at present, and that is unknown to science; we worked with the authority representative of the native community (apu) who lives and knows the reality of the communities. The results of the ancestral knowledge were the crops, customs, traditions of care of the nature, the technique of the chacrita (cultivation under the trees), and the construction of roads following the course of the trees; they make and use baskets, bundles, lapas, taken from the fruits of the trees, that once used disintegrate quickly in the soil. They practice the law of retribution to nature by planting native and exotic species in the deforested areas. In conclusion, the native communities of Totumberos have their own customs and traditions that should be emphasized.